Categorias Do Raciocínio Geográfico E Níveis De Conhecimento: O Uso De Indicadores De Alfabetização Geográfica (Iag) No Ensino Médio - Rodrigues, Pamella Bianca [UNIFESP] (2018)
The Present Research Discus The Role Of Geographical Literacy In The Development Of Geographic Reasoning. By Means Of The Comprehension Of The Geographic Literacy Levels Of The Students Of The Second Grade Of A Municipal High School In Santana De Parnaiba, State Of São Paulo. To Guide Our Observation, We Constructed Geographic Literacy Indicators (Gli), Which Are Composed By The Categories Of Geographic Reasoning And The Levels Of Geographic Knowledge. The Formulated Of The Indicators Was Based On Brazilian Studies On Geography Teaching: Castellar (2005, 2010a, 2010b And 2011); Callai (1999, 2005a, 2005b, 2010, 2011 And 2015); Cavalcanti (2005, 2010a, 2010b, 2011, 2012a And 2012b), Moraes (2010, 2012 And 2013) And Souza (2016), And Also On International Studies That Developed Methodologies To Verify The Levels Of Geographic Literacy: National Geographic (2002); Bascom (2011) And Dikmenli (2014 And 2015). The Students' Geographical Literacy Levels Were Observed Through Their Written Arguments In A Learning Sit